2023
DOI: 10.1111/bpa.13153
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling and prognostic factors of H3 K27M‐mutant spinal cord diffuse glioma

Abstract: H3 K27-altered diffuse midline glioma is a highly lethal pediatric-type tumor without efficacious treatments. Recent findings have highlighted the heterogeneity among diffuse midline gliomas with different locations and ages. Compared to tumors located in the brain stem and thalamus, the molecular and clinicopathological features of H3 K27-altered spinal cord glioma are still largely elusive, thus hindering the accurate management of patients. Here we aimed to characterize the clinicopathological and molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
(62 reference statements)
1
8
0
Order By: Relevance
“…Most tumors were located in the thalamus (53.12%). This observation aligns with existing literature emphasizing the diversity of diffuse midline gliomas across various locations and age groups [23][24][25]. Therefore, we conducted a more detailed analysis of both clinical and molecular characteristics across distinct subgroups, considering age and tumor location.…”
Section: Patients and Clinical Characteristicssupporting
confidence: 84%
“…Most tumors were located in the thalamus (53.12%). This observation aligns with existing literature emphasizing the diversity of diffuse midline gliomas across various locations and age groups [23][24][25]. Therefore, we conducted a more detailed analysis of both clinical and molecular characteristics across distinct subgroups, considering age and tumor location.…”
Section: Patients and Clinical Characteristicssupporting
confidence: 84%
“… 184 , 185 K27M mutation was found in 30% of children with high‐grade GBM, which was related to adverse clinical outcomes. 186 , 187 The decrease of H3K4me3 content in the promoter was also detected. 188 Christina et al.…”
Section: Abnormal Expression Of Histone‐modifying Enzymes and Human C...mentioning
confidence: 87%
“…184,185 K27M mutation was found in 30% of children with high-grade GBM, which was related to adverse clinical outcomes. 186,187 The decrease of H3K4me3 content in the promoter was also detected. 188 Christina et al found that the changes in gene expression of various methyltransferases, acetyltransferases, and deacetylases promoted the pathogenesis of GBM.…”
Section: Glioblastoma (Gbm)mentioning
confidence: 88%
See 1 more Smart Citation
“…Cancer has become the leading cause of death in China 1 . Gliomas are the most common primary brain tumor and are characterized by rapid malignant progression, poor response to radiotherapy and chemotherapy, high recurrence and mortality rates, and a poor prognosis [2][3][4][5][6] . Currently, the firstline orphan chemotherapy drug for glioma clinical treatment is temozolomide (TMZ), but some patients are not responsive to TMZ and responsive patients may develop drug resistance after treatment, thus limiting the clinical efficacy of TMZ 7,8 .…”
Section: Introductionmentioning
confidence: 99%